Influence of obstetrically-associated risk factors in assessing anal incontinence in patients post vaginal delivery - Spasova, Rosa; Tanturovski, Mile; Kocoski, Goran; Kjaev, Ivo; Stojoska Lazarova, Aleksandra; Karadjova, Dafina; Tofoski, Gligor; Jovanovska, Viktorija (Macedonian Association of Anatomists and Morphologists, 2018)
Introduction: Anal incontinence (AI) is an inconvenient and limiting medical condition that can cause social and hygienic problems, isolation, low self-esteem and low quality of life. The etiology is multifactorial. Women are eight times more affected than men and the reason is considered to be childbirth. In order to prevent this social, physical and psychological problem, it is necessary to define the risk factors leading to development of such symptoms in female patients after undergoing vaginal delivery. Factors that influence occurrence of anal incontinence in patients after vaginal delivery, have been categorized into obstetric, maternal and fetal factors. Objective: The purpose of this study is to determine the impact of individual obstetric risk factors on occurrences of anal incontinence in patients after vaginal delivery, and express it as anal score value. Materials and methods: We designed the study cross-sectional, and developed the research it at the University Clinic of Obstetrics and Gynecology, "Ss. Cyril and Methodius" University in Skopje, Macedonia, in a 3-month period, from August to November 2017. In this study, we engaged patients in their reproductive age, who had undergone at least one vaginal delivery. The degree of incontinence was determined using St. Mark's Anal Incontinence Score (SMIS). Results: In the examined segments, multi-parity (at least 2 vaginal births) increased by OR = 4.69 (95% CI 2.04-10.82) the patient's risk of having St. Mark’s score of ≥8 and this is statistically significant difference. Induced labor also reduced the likelihood of OR = 0.39 (95% CI 0.15-1.04) for St. Mark’s score of ≥8, but the difference was not a statistically significant one. Use of mediolateral episiotomy had protective significance against the risk of St. Mark score of ≥8. Conclusion: Results of this study show consistency with data published so far on the influence of obstetric risk factors on occurrences of anal incontinence in patients after vaginal delivery. Changes in anal incontinence are expressed in increased St. Mark’s score. Our study showed that the following factors had statistically significant impact on the score value: multi-parity, fetal macrosomia and perineal injury (grades 3 and 4).
Keywords: anal incontinence; vaginal delivery; risk factors; St. Mark's Anal Incontinence Score (SMIS)